Socialism vanquished, socialism challenged : Eastern Europe and China, 1989-2009 - Bandelj, Nina; Solinger, Dorothy J. (Oxford University Press, 2012)
This volume examines the 20-year aftermath of the 1989 assaults on established, state-sponsored socialism in the former Soviet bloc and in China. It brings together prominent experts on Eastern Europe and China to examine the respective trajectories of political, economic and social transformations that unfolded in these two areas, while also comparing the changes that ensued within the two regions.
Keywords: Europe, Eastern -- Politics and government -- 1989-; Post-communism -- Europe, Eastern.; Europe, Eastern -- Economic policy -- 1989-; China -- Politics and government -- 1976-2002.; China -- Politics and government -- 2002-; Post-communism -- China.; China -- Economic policy -- 1976-2000.; China -- Economic policy -- 2000-; Europe de l'Est -- Politique et gouvernement -- 1989-; Postcommunisme -- Europe de l'Est.; Europe de l'Est -- Politique économique -- 1989-; Chine -- Politique et gouvernement -- 1976-2002.; Postcommunisme -- Chine.; Chine -- Politique économique -- 1976-2000.; Chine -- Politique économique -- 2000-; POLITICAL SCIENCE -- Political Process -- General.; Economic policy; Politics and government; Post-communism; China; Eastern Europe; Government - Non-U.S.; Law, Politics & Government.; Government - Europe.; Since 1976; E-Books.; E-Reference.